Assessing the Effectiveness of al-Qarḍ al-Ḥasan Financing (A Case Study of Baitul Misykat Microfinance Institution in Aceh) - Hasnita, Nevi; Ayumiati, Ayumiati; Isnaliana, Isnaliana; Aini, Intan Qurratul; Amanatillah, Dara (Universitas Islam Negeri Jakarta, 2025)
Al-qarḍ al-ḥasan, a non-profit Islamic financing model, holds great potential in empowering marginalized communities. However, its practical implementation and long-term sustainability within Islamic microfinance institutions (IMFIs) remain limited in research, particularly in terms of integrating non-economic elements, such as spirituality. This study analyzes the effectiveness of al-qarḍ al-ḥasan financing implemented by Baitul Misykat in Aceh, with a focus on spiritual development as a key strategy for economic empowerment. Using a qualitative phenomenological case study approach, data were collected through in-depth interviews, field observations, and document analysis. Findings show that al-qarḍ al-ḥasan's financing significantly contributes to the economic empowerment of small traders. Effectiveness is influenced by four interrelated factors: strict beneficiary selection, continuous business monitoring, innovative non-monetary repayment incentives, and integration of spiritual development programs. These elements foster borrower discipline, ethical conduct, and business sustainability. The involvement of government officials, religious leaders, and economists enhances institutional capacity and community confidence. This study introduces a novel perspective by demonstrating how spiritual mechanisms can be synergized with Islamic finance to shape ethical entrepreneurial behavior. It offers a scalable and replicable model for IMFIs, suggesting that integrating ethical-spiritual education into financial systems may support poverty alleviation and inclusive development strategies in Muslim-majority societies. Abstrak Al-qarḍ al-ḥasan, sebagai model pembiayaan sosial, memiliki potensi besar dalam memberdayakan komunitas marjinal. Namun, implementasi praktis dan keberlanjutannya pada lembaga keuangan mikro syariah (LKMS) masih minim kajian, terutama terkait integrasi aspek non-ekonomi seperti spiritualitas. Studi ini menganalisis efektivitas pembiayaan al-qarḍ al-ḥasan yang diterapkan oleh Baitul Misykat di Aceh, dengan fokus pada pengembangan spiritual sebagai strategi utama dalam pemberdayaan ekonomi. Menggunakan pendekatan studi kasus fenomenologis kualitatif, data dikumpulkan melalui wawancara mendalam, observasi lapangan, dan analisis dokumen. Hasil penelitian menunjukkan bahwa pembiayaan al-qarḍ al-ḥasan secara signifikan berkontribusi terhadap pemberdayaan ekonomi pedagang kecil. Efektivitasnya dipengaruhi oleh empat faktor yang saling berkaitan: seleksi penerima manfaat yang ketat, pengawasan usaha yang berkelanjutan, insentif pelunasan non-moneter yang inovatif, dan integrasi dengan program pengembangan spiritual. Unsur-unsur ini mendorong kedisiplinan, perilaku etis, dan keberlanjutan usaha. Keterlibatan pemerintah, tokoh agama, dan ekonom turut memperkuat kapasitas lembaga dan kepercayaan masyarakat. Studi ini menghadirkan pendekatan baru dengan menunjukkan bagaimana pembinaan spiritual dapat disinergikan dengan pembiayaan syariah untuk membentuk perilaku kewirausahaan yang etis. Temuan ini menawarkan model kebijakan yang dapat dikembangkan dan direplikasi oleh LKMS, serta menunjukkan bahwa integrasi pembinaan etika-spiritual dalam sistem keuangan dapat mendukung strategi pengentasan kemiskinan dan pembangunan inklusif di masyarakat Muslim.